2003
DOI: 10.1152/japplphysiol.00128.2003
|View full text |Cite
|
Sign up to set email alerts
|

A feedback-controlled treadmill (treadmill-on-demand) and the spontaneous speed of walking and running in humans

Abstract: A novel apparatus, composed by a controllable treadmill, a computer, and an ultrasonic range finder, is here proposed to help investigation of many aspects of spontaneous locomotion. The acceleration or deceleration of the subject, detected by the sensor and processed by the computer, is used to accelerate or decelerate the treadmill in real time. The system has been used to assess, in eight subjects, the self-selected speed of walking and running, the maximum "reasonable" speed of walking, and the minimum rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 16 publications
4
79
0
1
Order By: Relevance
“…The observed trend is consistent with the literature in that motion cueing can often enhance perception of self-motion [7], [11], [12], [25], [29], [46]. However, the lack of significant benefit of motion cueing on self-motion perception in the current study suggests the need for further development of these prototype-like interfaces.…”
Section: Sensation Of Self-motionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observed trend is consistent with the literature in that motion cueing can often enhance perception of self-motion [7], [11], [12], [25], [29], [46]. However, the lack of significant benefit of motion cueing on self-motion perception in the current study suggests the need for further development of these prototype-like interfaces.…”
Section: Sensation Of Self-motionsupporting
confidence: 91%
“…User-powered motion cueing can help create a simple and relatively inexpensive locomotion system, whereas the classic approach of using computer-driven and motorized platforms requires large and expensive setups to create motion that is similar to real-world motion. Moreover, interfaces that utilize user-powered motion cueing can be less dangerous and technically complex than large motorized platforms, which often require safety harnesses [7], [8] because they use simple perceptual deceptions instead of physically moving users in order to give them the feeling of movement. For example, Beckhaus and Riecke both developed seated interfaces with active motion cueing so that users could navigate in 3D environments without the space requirements of larger physical system or where walking was infeasible [9]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…Wheat and his colleagues 2004;2005;Wheat, 2005) have reported comparisons of running overground, on a standard treadmill and on an on-demand treadmill, in which the belt speed adapts to the speed of the runner (Minetti et al, 2003). In their second study, the treadmill-on-demand, for which the treadmill speed is not constant, was added to the overground and treadmill conditions (Wheat, 2005;Wheat et al, 2005).…”
Section: Variability In Basketball Shootingmentioning
confidence: 99%
“…Nevertheless, while metabolic-energy consumption per se may not be the primary stimulus for eliciting gait transitions, this does not exclude the possibility that the speeds and associated gaits favourable to lowering the metabolic cost of locomotion have probably been selected for through evolution to make better use of the limited energy sources available. In this respect, it has been shown that humans and other animals will avoid those speeds that result in unnecessarily high costs of locomotion (Hoyt & Taylor 1981;Minetti et al 2003).…”
Section: (A) Gait Selectionmentioning
confidence: 99%